Theodicy, Undeserved Suffering, and Compassionate Solidarity: An Interdisciplinary Reading of Hwang Sok-Yong’s The Guest - Kim, Young Hoon (Religions, 2020)
The author explores theological questions regarding the Korean novelist Hwang Sok-yong’s The Guest from interdisciplinary perspectives. This paper analyzes the novel in relation to the emotional complex of han as understood in Korean minjung theology, the political theology of Johann Baptist Metz, and Ignacio Ellacuría’s liberation theology. Drawing upon the perspectives of Korean, German, and Latin American scholars, this approach invites us to construct a discourse of theodicy in a fresh light, to reach a deeper level of theodical engagement with the universal problem of suffering, and to nurture the courage of hope for human beings in today’s stressed world. Contemplating the concrete depiction of human suffering in The Guest, the paper invites readers to deepen their understanding of God in terms of minjung theology’s thrust of resolving the painful feelings of han of the oppressed, Metz’s insight of suffering unto God as a sacramental encounter with God, and Ellacuría’s idea of giving witness to God’s power of the resurrection in eschatological hope. The paper concludes that the immensity of today’s human suffering asks for that compassionate solidarity with the crucified today which can generate hope in the contemporary milieu.